Study the Effect of Different Ranges of Temperatures and pH on Pathogenic Fungi Growth Trichophyton rubrum and Trichophyton mentagrophytes Which Caused the Onychomycosis - HASANAIN YASEEN MARZOQ (Al-Qadisiyah Journal of Pure Science, 2017)
The swabs were taken from toenails of active edges for the infected persons, who recorded in AL-Hussein education hospital in AL-Samawa city to study the effect of different ranges of temperatures and pH on pathogenic fungi growth Trichophyton rubrum and Trichophyton mentagrophytes which caused the onychomycosis for the period (2/7 – 2 /8/2012) with 25 sample, and the study shows that increase of temperatures proportional with fungal growth, and average reached colonies diameters of fungus Trichophyton rubrum (69.44, 80.28, 86.01, 85.32, 78.36 and 61.33) mm in temperatures (25, 30, 35, 40, 45 and 50) oC respectively, and average reached colonies diameters of fungus Trichophyton mentagrophytes (65.11, 74.13, 82.59, 83.88, 71.41 and 56.07) mm in temperatures (25, 30, 35, 40, 45 and 50) oC respectively, and the study shows also that pH=6 the perfect for fungal growth, and average reached colonies diameters of fungus Trichophyton rubrum (19.22, 29.91, 59.26, 48.04 and15.55) mm in pH (4, 5, 6, 7 and 8) respectively, and average reached colonies diameters of fungus Trichophyton mentagrophytes (17.09, 26.33, 57.76, 44.55 and 13.71) mm in pH (4, 5, 6, 7 and 8) respectively.